Rationality and irrationality in the history of continental drift: was the hypothesis of continental drift worthy of pursuit? - Šešelja, Dunja; Weber, Erik (Studies in History and Philosophy of Science, 2012)
The revolution in geology, initiated with Alfred Wegeners theory of continental drift, has been the subject of many philosophical discussions aiming at resolving the problem of rationality underlying this historical episode. Even though the debate included analyses in terms of scientific methodology, applications of concrete accounts of epistemic justification to this case study have been rare. In particular, the question as to whether Wegeners theory was epistemically worthy of pursuit in the first half of the twentieth century, that is, in its early development, remained open or inadequately addressed. The aim of this paper is to offer an answer to this question. The evaluation of Drift will be done by means of an account of theory evaluation suitable for the context of pursuit, developed in šešelja and Straßer (accepted for publication). We will argue that pursuing the theory of continental drift was rational, i.e., that it was irrational to reject its pursuit as unworthy